Penerapan Model Project Based Learning untuk Meningkatkan Hasil Belajar Peserta Didik di Kelas V SD - Dewi, Elma; Indrawati, Tin (TSAQOFAH, 2023)
This research is motivated by the low thematic learning outcomes. This study aims to described the improvement of student learning outcomes in integrated thematic learning using the Project Based Learning (PjBL) model in class V SDN 07 Belakang Tangsi, Padang. Integrated thematic learning is learning that uses themes to link several sybjects so that the can provide meaningful experiences to students. This research method is a classroom action research (PTK) using qualitative and quantitative approaches. The subjects of this study were class teachers as observers, researchers as practitioners, and 27 students of class V SDN 07 Belakang Tangsi. The result of this study are: (1) The percentage of RPP assessments has increased from 77,7% in cycle I to 94,44% in cycle II. (2) In the teacher aspect, it increased from 79,68% in cycle I to 96,87% in cycle II. (3) In the aspect of students, it increased from 79,68% in cycle I to 96,87% in cycle II. and (4) In the student learning outcomes increased from 73,48 in cycle I to 88,2 in cycle II.